A interatividade e a interface gráfica em um ambiente virtual de aprendizagem - Machado Junior, Felipe Stanque (2007)
This study tries to bring considerations that help to analyze de effectiveness of a significant relationship among subjects that involves distance education, virtual learning environments and interactivity. As general objective, discusses the contribution of virtual learning environments to the educational process that hapens at the distance starting from the evaluation of the potentialities of the environment to support the communication and the interaction through the graphical interface. This system can present certain characteristics in the visual/textual discourse of its interface that are interactivity and interactions potentializer in the educational process that develops through the distance. Taking the virtual learning environment denominated Moodle as example to be analyzed, the research method envolves a qualitative approach, with basic, exploratory and descriptive nature that uses intentional samples. From these samples, the data collection for analysis is made by observation, and the evaluation of the samples has as parameters foundations for promotion of the mutual interaction and for interactive products conception presented in the theoretical revision. Starting fromthe evaluation of the Moodle and from the comparison of it with common types of web sites it is possible to evidence that the graphical interface has important influence in the communication and the potentialization of the interactive character of the virtual learning environment, being basic that the flexibility of the interface is used to advantage under determined criteria